Factors affecting SMEs successful utilization of tax incentives in manufacturing sectors / Nadiah Abd Hamid, Rohaya Mohd Noor and Mustaffa Mohamed Zain. - Abd Hamid, Nadiah; Mohd Noor, Rohaya; Mohamed Zain, Mustaffa (Universiti Teknologi MARA Cawangan Selangor, 2011)
This study aimed to determine the key factors associated with successful utilization of tax incentive and to further investigate which factors were significant via the logistic approach. Using the convenient sampling, 125 SMEs in the manufacturing sector were selected as samples. The findings showed four factors; capital investment, business strategies, government support and environment were significant in attributing to successful utilization of tax incentives. A further analysis using the logistic approach was extended to determine the underlying factors of why some SMEs were able to utilize the tax incentives, whilst others were not. The results from the logistic approach revealed that factors related to the governance of companies had significant influence on the ability of the company to effectively utilize the tax incentives. This study used both primary and secondary data and employed methods, such as, survey and real financial data analysis retrieved from companies’ financial statements.